SAT0037 Iguratimod ameliorates bleomycin-induced alveolar inflammation and pulmonary fibrosis in mice by suppressing expression of mmp-9. (12th June 2018) - Zhao, L.; Mu, B.; Zhou, R.; Huang, C.
Abstract : Background: Interstitial lung disease (ILD) occurs in 15% of patients with connective tissue diseases (CTD) It contributes significantly to morbidity and mortality, and is difficult to manage (1) . Despite advances in management strategies, CTD-ILD have a significant adverse effect on quality of life and is still a leading cause of mortality, highlighting an urgent need for optimal treatment regimens. It is known that inflammatory cytokines played an important role in alveolitis and the development of pulmonary fibrosis (2) . Iguratimod (IGU) has a reported effect on preventing the inflammatory processes by inhibiting the production of various inflammatory cytokines (3) . Objectives: To investigate the potential therapeutic efficacy of IGU on mouse model of bleomycin (BLM) induced pulmonary fibrosis. Methods: A total of 75 C57BL/6 mice were randomly and evenly divided into control group, BLM (5 mg/kg) group, BLM +IGU (90 mg/kg) group, BLM +methylprednisolone (MP, 10 mg/kg) group and BLM +pirfenidone (PF, 100 mg/kg) group. The mice were sacrificed on day7, day 14, day 28 respectively. The lung tissue was examined by Hematoxylin and eosin staining and Masson staining to evaluate the degree of alveolitis and fibrosis, and plasma cytokines were measured. Results: Histopathological results showed that IGU attenuated BLM-induced alveolar inflammation and decreased collagen deposition in lung tissue from day 7 till day 28. Both the pathological alveolitis scores and fibrosis scores in drug treated group (IGU group, MP group and PF group) were decreased dramatically compared with BLM group on day7, day 14 and day 28 respectively (p<0.05). There were no statistical significances among those three groups. Cytokine profile showed that IGU decreased the level of tumour necrosis factor-α (TNF-α), interleukin (IL)−1, IL-6 and matrix metalloproteinase (MMP)−9 which were up-regulated by BLM on day 7, day 14 and day 28 respectively (p<0.05). Furthermore, there is a strong correlation between the severity of the pulmonary fibrosis and the plasma MMP-9 levels (&x2194;&x2194;=0.836, p<0.001). Conclusions: IGU was effective in suppressing BLM-induced alveolar inflammation and pulmonary fibrosis, and it has the equal anti-inflammatory and anti-fibrotic effects as MP or PF. The therapeutic effects by IGU may be attributed to the inhibition of MMP-9 either directly or indirectly. Therefore, IGU presents as a promising agent for pulmonary fibrosis treatment. References: [1] Demoruelle MK, Mittoo S, Solomon JJ. Connective tissue disease-related interstitial lung disease. Best practice & research Clinical rheumatology2016;30:39–52. [2] Luzina IG, Todd NW, Sundararajan S, Atamas SP. The cytokines of pulmonary fibrosis: Much learned, much more to learn. Cytokine2015;74:88–100. [3] Mucke HA. Iguratimod: a new disease-modifying antirheumatic drug. Drugs of today2012;48:577–86. Disclosure of Interest: None declared